Managing Children's Anxiety During COVID-19 Pandemic: Strategies for Providers and Caregivers - Kang, Ying Qi; Lim, Tammy S. H.; Ragen, Elizabeth Sarah; Tan, Mae Yue; Aishworiya, Ramkumar (Frontiers in Psychiatry, 2020)
The Coronavirus Disease 2019 pandemic by virtue of its sudden, unprecedented and widespread nature, has led to a multitude of psychological effects on individuals across societies. This includes anxiety which has important implications on the daily functioning, physical and mental health of individuals. Children are a vulnerable group of the population who can experience anxiety which potentially can lead to long-lasting implications on their health for years to come. It is thus important that their caregivers, including parents and healthcare professionals be aware of strategies that can help with anxiety in children. This article discusses anxiety in children in the context of the COVID-19 pandemic and outlines strategies that may be helpful